Investigating Compassion as Moderating Role: Psychological Contracts Breach on Nurse’s Turnover Intention - Safitri, Dina (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This research examines the relationship between turnover intention as the impact of psychological contract breaches that are moderated with compassion Design/methodology/approach: The study, based on 216 respondents in the Indonesian healthcare industry with a non-probability sampling, employs the advanced statistical tool SmartPLS4 to analyze the individual and combined effects of these factors on the intention of turnover. Research Findings: The findings indicate a significant positive correlation between nurses' intentions to leave and their compassion, indicating that more significant percentages of compassion are associated with a higher risk of leaving. The data challenge common assumptions by showing that the direct impact of a breach of psychological contract on the intention to leave is not substantiated, contrary to expectations. Additionally, the study demonstrates a weak association between psychological contract breach and compassion significantly correlated with turnover intention. Theoretical Contribution/Originality: Compassion as the moderating role in Indonesian healthcare research is still scarce in the literature. The research findings imply that compassion may alleviate the adverse effects of psychological contract breaches, providing valuable insights for the healthcare industry to tackle turnover issues. This research enriches our understanding of turnover intention within the nursing context, highlighting the significance of individual and environmental factors. The application of SmartPLS4 enhances the investigation of these relationships among nurses in Indonesia. Keywords: Psychological contract breach, compassion, turnover intention, human resource, employment relationship